OPTIMIZATION OF PRODUCTION ON WELL-11 WITH PUMP SETTING DEPTH VARIATION IN ELECTRICAL SUBMERSIBLE PUMP (ESP) METHOD AT K-U FIELD - Trimadona, Trimadona; Hendra Budiman, (Jurnal Cakrawala Ilmiah, 2023)
Well 11 is a production well in the K-U field that has a decreased pressure so it requires an artificial lift levitation method so it can help produce fluids to the surface. The use of Electrical Submersible Pump method has an actual flow rate 665 bpd less than flow rate of curve IPR in a mount of 915 bpd. After the evaluation of variation value pump setting depth, the redesign pump discharged with a different psd variation. After redesign the depth of the pump, it obtained 5500 psd ft with the amount of stage 343, the type of the pump from IND-750 with operation frequency 60Hz produce flow rate 905 bpd.